If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -8 = 2(3x + -76) Reorder the terms: -8 + 3x = 2(3x + -76) Reorder the terms: -8 + 3x = 2(-76 + 3x) -8 + 3x = (-76 * 2 + 3x * 2) -8 + 3x = (-152 + 6x) Solving -8 + 3x = -152 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -8 + 3x + -6x = -152 + 6x + -6x Combine like terms: 3x + -6x = -3x -8 + -3x = -152 + 6x + -6x Combine like terms: 6x + -6x = 0 -8 + -3x = -152 + 0 -8 + -3x = -152 Add '8' to each side of the equation. -8 + 8 + -3x = -152 + 8 Combine like terms: -8 + 8 = 0 0 + -3x = -152 + 8 -3x = -152 + 8 Combine like terms: -152 + 8 = -144 -3x = -144 Divide each side by '-3'. x = 48 Simplifying x = 48
| 17x+5=17x-5 | | Graphy=2x+1 | | -4(3x+9)+3x=6-4(x-3) | | -4x-6y=-18 | | 2piR=x | | 3/5n-4/5=1/5n | | 4(x^3-4X)=0 | | (7rs^2)(-3r^5s^4)= | | 1900-6p=-2(10n+7) | | 6=-12(10n+7) | | 7d-6=22 | | -2v=-6-4t | | A=2x-6 | | 1x+2x=79 | | 4t-8=t-5 | | 2x=5y-108 | | -5(x+3)-(9x-4)=x-5+3 | | x-10+2x-221+0.5x+5=180 | | z(z-3)+2(z+3)=18 | | 5h+4=4h+11 | | w(20w-73)=-63 | | 6(x^2+x-20)=0 | | 5n+43=-2(1-7n) | | 6y-8=4y+2 | | 7+7x=7+8x | | x+5x+4x-6=180 | | 7=4y-2y+1 | | 3v-5=16 | | z^2-30z+c=0 | | (13b-7)-3(4b+3)=-6 | | 4x-5=(x-1) | | 3.5(x-2)=12-.5x |